2013
DOI: 10.4103/0975-1475.119777
|View full text |Cite
|
Sign up to set email alerts
|

Lip prints: The barcode of skeletal malocclusion

Abstract: Introduction:In orthodontics, apart from essential diagnostic aids, there are so many soft tissue analyses in which lips are major part of concern. However, lip prints have never been used in orthodontics as diagnostic aid or forensic tool. Therefore, this study was designed to explore the possible association of lip prints with skeletal malocclusion.Materials and Methods:A sample of 114 subjects in the age group of 18-30 years, from North Indian adult population were selected on the basis of skeletal class I,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 10 publications
2
18
1
Order By: Relevance
“…This was in accordance to the study done by Raghav et al . [8] and Madhusudan et al .,[9] who reported the same predominance in patients with complete permanent dentition.…”
Section: Discussionmentioning
confidence: 81%
“…This was in accordance to the study done by Raghav et al . [8] and Madhusudan et al .,[9] who reported the same predominance in patients with complete permanent dentition.…”
Section: Discussionmentioning
confidence: 81%
“…In a similar study by P Raghav et al in 2013 [8], to explore the association of lip print and malocclusion in north Indian population, concluded that no sexual dimorphism was present and that vertical lip pattern was predominant in skeletal class III malocclusion.…”
Section: Resultsmentioning
confidence: 95%
“…This was in accordance to the study done by Raghav et al . [ 4 ] and Madhusudan et al .,[ 15 ] who reported the same predominance in individuals with complete permanent dentition. The patterns that were seen predominantly in children with mesial step are both Type IV (reticular) and Type V (irregular) patterns, with the predominant pattern seen in children with distal step being Type IV (reticular) pattern and for flush terminal plane being Type I (complete vertical) pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Cheiloscopy is one of the analytical tools that are used in forensic dentistry. Studies were performed to assess the link between these lip prints and permanent occlusal relationship,[ 4 5 6 ] but its association with terminal plane of primary dentition has not been reported. Hence, this study was aimed to assess the correlation between different cheiloscopic patterns with the terminal planes in deciduous dentition.…”
Section: Introductionmentioning
confidence: 99%